The immunomodulatory potential of Leonurus cardiaca extract in relation to endothelial cells and platelets. Issue 3 (April 2017) - Sadowska, Beata; Micota, Bartłomiej; Różalski, Marek; Redzynia, Małgorzata; Różalski, Marcin
The immunomodulatory activity of Leonurus cardiaca L. polyphenol-rich extract (LCE) was tested in vitro on HUVECs to explore its potential therapeutic usefulness in the treatment of inflammatory lesions. The phytochemical composition of LCE, its antioxidant and cytotoxic activity, and the influence of LCE on NO and platelet-activating factor (PAF) secretion by HUVECs and platelet aggregation were all assessed. Total polyphenol contents in LCE reached 137.0 ± 0.8 mg/g, with hydroxycinnamic acid derivatives as the predominant phenolic compounds. LCE expressed antioxidant capacity, which was, however, 13- to 16-fold lower than the antioxidant activity of ascorbic acid. The plant extract was not cytotoxic up to a concentration 4500 µg/ml and did not exhibit proapoptotic activity. LCE significantly increased NO production in HUVECs in a concentration-dependent manner and led to the inhibition of PAF secretion induced by staphylococcal peptidoglycan. The extract used at the concentration of 100 µg/ml significantly reduced platelet aggregation in the presence of arachidonic acid. We provide in vitro data demonstrating the immunomodulatory potential of LCE, which may be beneficial in preventing the development of difficult-to-treat inflammatory lesions within chronically infected tissues.